FACTORS INFLUENCING FEMALE UNIVERSITY STUDENTS TO ENGAGE IN PROSTITUTION - Mugane, Joshua Juma (Uniqbu Journal of Social Sciences, 2023)
This study was conducted with an aim of determining the possible factors that influence female university students to engage in prostitution. A longitudinal research design was employed during the study, so as to collect the intended data/information within a planned period of time. The collected information and data were gathered from a sample size of 25 female university students, which was obtained through snowball sampling. With the use of semi-structured interview guide in accumulating data, the obtained findings were analyzed qualitatively, indicating the quotes of the respondents as obtained during the study. The analyzed and discussed data reveal that female university students often engage in prostitution due to several influential factors. Such factors include peer influence, sexual addiction, having a desire to attain satisfaction amidst insufficiencies, wanting to revenge after passing through several relationship breakups or after being infected with HIV/AIDS, and considering oneself as unworthy after a number of disappointments. Also, due to the diverse life experiences and psycho-emotional conditions, the female university students have finally engaged themselves in prostitution. For those cases, there is also a need of assisting all those who have engaged themselves in prostitution, so that they may not encounter other complications. This can take place through provision of psychotherapies and counselling services, together with psycho-educational sessions concerning the dangers and hazardous effects of prostitution. And also, it may be implemented through teaching them problem solving and crises intervention techniques, so that when they face insufficiencies and challenges (including financial matters), they would not turn into prostitution as a mean of finding solutions.